Associations between depression and cognition, mild cognitive impairment and dementia in persons with diabetes mellitus: A systematic review and meta-analysis. (March 2022) - Chow, Yeng Yan; Verdonschot, Milou; McEvoy, Claire T.; Peeters, Geeske
Highlights: Depression is associated with poorer cognitive function in persons with diabetes. Depression is associated with higher dementia risk in persons with diabetes. The role of timing and frequency of depressive episodes has yet to be explored. The potential mitigating role of antidepressive treatment has yet to be explored. Abstract: Aims: This systematic review aimed to examine whether persons with diabetes and depression had poorer cognition and higher dementia risk than persons with diabetes only. Moreover, the impact of timing, frequency of depressive episodes throughout life, and antidepressant treatment were examined. Methods: PubMed, Embase and PsycINFO were searched to obtain observational studies between August 2015 and June 2021 that examined the association between depression and cognition, mild cognitive impairment or dementia in people with diabetes. Studies published before August 2015 were retrieved from a previous systematic review. Findings were pooled using meta-analyses. Results: 10 out of 19 included articles were appropriate for the meta-analyses. Persons with diabetes and depression experienced greater declines in executive function (SMD = −0.39 (−0.69, −0.08)), language (SMD = −0.80 (−1.52, −0.09)), memory (SMD = −0.63 (−1.12, −0.14)) and overall cognition (SMD = −0.77 (−1.33, −0.20)), and greater dementia risk (HR = 1.82 (1.79, 1.85)) than persons with diabetes only. No significant differences were observed for complex attention. No studies examined the role of timing and frequency of depressive episodes and antidepressant treatment. Conclusion: In persons with diabetes, depression is associated with worse cognition and higher dementia risk. The potential mitigating effect of antidepressant treatment remains unclear.